2011
DOI: 10.1111/j.1432-2277.2011.01389.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting operational tolerance after pediatric living-donor liver transplantation: impact of early post-transplant events and HLA match*

Abstract: Summary Pediatric recipients of living‐donor liver transplants (LDLT) can often discontinue immunosuppression (IS). We examined factors affecting development of operational tolerance (OT), defined as off IS for >1 year, in this population. A historic cohort analysis was conducted in 134 pediatric primary semi‐allogeneic LDLT. Multivariate logistic regression analysis was used. The frequency of peripheral regulatory T cells (Tregs) was determined at >10 years post‐Tx by FACS analysis. IS was successfully discon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 48 publications
1
50
0
1
Order By: Relevance
“…Normal liver function was initially observed in some patients after required immunosuppression withdrawal due to complications such as PTLD or noncompliance . Multiple studies have examined this phenomenon, although pediatric‐specific studies have been limited (Table ) . These reports demonstrated that a proportion of carefully selected LT recipients (15%‐60%) can be successfully weaned off immunosuppression with normal allograft function 14‐120 months after medication discontinuation .…”
Section: Tolerancementioning
confidence: 99%
“…Normal liver function was initially observed in some patients after required immunosuppression withdrawal due to complications such as PTLD or noncompliance . Multiple studies have examined this phenomenon, although pediatric‐specific studies have been limited (Table ) . These reports demonstrated that a proportion of carefully selected LT recipients (15%‐60%) can be successfully weaned off immunosuppression with normal allograft function 14‐120 months after medication discontinuation .…”
Section: Tolerancementioning
confidence: 99%
“…This is particularly surprising given the widely held belief that relative to other transplanted organs livers are more resistant to the long-term injurious effects of rejection and more predisposed to the development of tolerance. However, a number of investigators have examined spontaneously tolerant patients or conducted trials in which patients have undergone closely supervised drug withdrawal; a scenario in which several studies have suggested that in carefully selected cohorts of liver transplant recipients the incidence of spontaneous tolerance may approach or even exceed fifty percent (19, 26, 27). These studies have led to the description of a number of potential biomarkers of liver allograft tolerance.…”
Section: Biomarkers In Spontaneously Tolerant Kidney Transplant Recipmentioning
confidence: 99%
“…In our cohort, the patients had received similar immunosuppression in early phase after LT. On the other hand, the immunosuppression was individualized for the renal or infectious complication, or for the operational tolerance after the early postoperative period [46][47][48]. In addition, a large number of HCV patients who underwent LT were treated for recurrent HCV with IFN-based therapy, which is reported to contribute to develop ACR [49].…”
Section: Discussionmentioning
confidence: 99%